Molecular Fish Species Identification of Commercial Traditional Seafood Products in the Malaysian Market - Fatin Qurratu’aini, Zaini; Danial Hariz, Zainal Abidin; Nor Rahman, Aifat; Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain (The Malaysian Society of Applied Biology, 2025)
Seafood is a vital source of protein, multivitamins, and essential fatty acids, particularly omega-3. However, seafood fraud is becoming a growing threat to food safety in Malaysia. This study reports on the molecular identification of fish species in various seafood products collected from different regions in Malaysia. DNA barcoding employing a ~500 bp fragment of the mitochondrial cytochrome c oxidase I (COI) gene was used to identify 46 samples. Successfully amplified and identified samples accounted for 48% of the analysed fish products. Sardinella species were most commonly used in traditional Malaysian products, especially in the east coast states. Interestingly, we found regional variations in fish species used for the same traditional products, highlighting the diversity of local preferences and resource availability. DNA barcoding with the COI marker was found to be effective for the rapid identification of fish species in processed foods, which could enhance food safety and consumer confidence. Although no toxic fish substitutions were detected, the results highlight the need for more comprehensive labelling practices in the Malaysian seafood market. This study emphasises the potential of molecular techniques in addressing food fraud concerns and improving seafood traceability.